Pelvic floor dysfunction in female triathletes - Mkhombe, Welile (Department of Obstetrics and Gynaecology, 2018)
Background: In the past few decades, an increasing number of women have been participating in high-impact sports which involves jumping, landing and/ or running activities. Recent data have shown, however, that this kind of activity might be associated with adverse effects, including pelvic floor disorders. Nevertheless, there is very little in the literature about pelvic floor effects associated with endurance sports where high-impact exercise is performed at submaximal intensity for prolonged periods of time. Objective: The primary objective of the present paper is to describe the prevalence of pelvic floor dysfunction (PFD) in a female triathlete population. Methods: An anonymous on-line survey was administered from September 2015 to March 2016 to women who self-identified as triathletes. We used two validated questionnaires: the Pelvic Floor Distress Inventory Questionnaire short form (PFDI) and the Pelvic Floor Impact Questionnaire short form (PFIQ). In addition, respondents were asked for demographics (age, height, weight, occupation), general health status (medical history, pelvic/abdominal surgical history, pregnancy and birth history) as well as sport practice characteristics (duration of training, level of competition, number of hours spent per week swimming, cycling, and running), so as to characterise these female triathletes. The survey remained active online for seven months, during which time the majority of responses were obtained from having our survey on the IRONMAN December 2015 newsletter. The balance of responses came from various triathlon clubs which we had approached within Western Cape Province. Results: Sixty-seven female triathletes responded to the online survey which we designed on SurveyMonkey. The respondents were between the ages of 22 and 56 years, the mean being 37 years. They had a mean BMI of 22.6 kg/m2. None of them had any medical conditions known to increase the risk of PFD. Of the known surgical history risk factors, 74.6% had had no previous pelvic or abdominal surgery. In the cohort, 69.2% were nulliparous and 30.8% parous. Most of the respondents competed in the recreational age group (70.4%), compared with 29.6% who described themselves as being in the competitive age group. Over 94.4% of the participants had been involved in triathlon training for a period of more than 6 months. At the peak of their training, athletes described their weekly training regime as comprising a mean of 5.4 hours running, 3.9 hours swimming and 9.1 hours cycling. Of those who performed any form of 'core exercises', 29.6% performed pelvic floor exercises, 16.7% yoga, and 25.9% Pilates as part of their routine training. Eighty-two per cent of the triathletes had competed in the half IRONMAN and 37.8% in at least one full IRONMAN competition. The PFDI revealed a number of commonly occurring pelvic floor symptoms. The most reported urinary symptoms were urinary frequency, stress urinary incontinence (SUI) and urge urinary incontinence (UUI) (45.8%, 33.3% and 37.5%, respectively). The most reported colorectal symptoms were incomplete bowel emptying (41.7%), faecal urgency (43.8%), and flatal incontinence (41.7%). Pelvic organ prolapse symptoms were least reported, but those who had symptoms mostly experienced heaviness or dullness in the pelvic area (33.3%), pressure in the lower abdomen (31.3%) and a need for vaginal/rectal digitation in order to have or complete a bowel movement (25%). It was noteworthy to find that the nulliparous triathletes had more pelvic floor symptoms than the parous group. A higher prevalence of colorectal/rectal symptoms were reported by those who had had forceps deliveries. Colorectal symptoms were found to be slightly more prevalent in those who performed any pelvic floor exercises (PFE), yoga or Pilates than amongst those who did not. Even with the myriad symptoms reported, these women were not significantly bothered by their symptoms. Conclusion: It is apparent that PFDs are prevalent in the population reviewed, although the majority of individuals did not seem to be bothered by the symptoms that also did not appear to interrupt training or quality of life. For those who are concerned or troubled by the symptoms, it would be beneficial for them to be identified early so that management options can be offered to relieve the symptoms.